School physical structure as a determinant of quality in education in professional schools in Ceará: between reality and myth (Research, Society and Development, 2020)
Access to selected good conditions is indicated by educational agents as essential for the performance of pedagogical functions in the provision of education. They are often treated as determining factors for the quality of teaching and the definition of elementary education or the student's academic success. What the State of Ceará shows in the national scenario as a reference for educational quality, in particular, with reference to the professional education policy integrated with high school, or the objective of this research was to evaluate whether the physical structure of the building, as well as the didactic resources- Pedagogical factors are available that determine the quality of education in this type of teaching. It is a qualitative work, of a descriptive nature, done through bibliographic survey, documentary research, observation on the spot and application of a questionnaire, in the form of a comparative study between 10 State Schools of Professional Education (EEEP), being 5 with high performance and 5 with low performance, in the results of the evaluations of the Permanent System of Evaluation of Basic Education of the State of Ceará (SPAECE). The study discards the factor of physical structure, however, in isolation, as a determining factor in the provision of quality education, as well as a driver of school success, which considers the results of external evaluations. In addition, it presents as a contribution to academic, scientific and professional training, while conceiving the theoretical topics in the construction of new research to improve student learning.